Hubungan Nilai-nilai Pola Pikir dan Perilaku Ramah Lingkungan Siswa Sekolah Dasar Adiwiyata - Yudhistira Kusuma; Hanson Endra Kusuma (RUAS (Review of Urbanism and Architectural Studies), 2020)
The declining quality of the environment lately requires a change in human’s environmental value and behavior. This change can be achieved through environmental education in schools. Indonesia has recently promoted the Adiwiyata school program to encourage environmental education. This study aims to reveal the dimensions of value (NEP) and behavior (GEB) that occur in students at Adiwiyata school and explain the relationship between the two to evaluate the extent to which Adiwiyata's concepts can interfere with students' thought patterns and behavior. Through principal component analysis and factor analysis, six dimensions of student’s NEP were found in Adiwiyata Elementary School, respectively: "Destructive Interventions", "Conservative Interventions", "Exploitation of Nature", "Environmental Education", "Sustainable Environments", and "Environmental Insights". Besides, four dimensions of student’s GEB were found at Adiwiyata Elementary School, respectively: "Pro-Environmental Attitudes (Individual)", "Pro-Environmental Attitudes (Group)", "Waste of Natural Resources & Energy", and "Efficiency of Natural Resources & Energy". Furthermore, correlation analysis shows that these values and behavior tend to only be realized in the school environment.